Faktor-Faktor yang Berhubungan dengan Rendahnya Cakupan Asi Eksklusif pada Ibu Bekerja di Wilayah Puskesmas Penfui. - Mediana Tabelak; Grouse T, S. Oematan; Anna H. Talahatu (Quantum Wellness : Jurnal Ilmu Kesehatan, 2024)
Breast milk (breast milk) is the best nutrition for babies, the low coverage of exclusive breastfeeding is a threat to the growth and development of children, breastfeeding is the right of every mother, and exclusive breastfeeding to newborns is one of the efforts to prevent infectious diseases, malnutrition problems, and infant death. due to many influencing factors, namely the lack of maternal knowledge about breastfeeding, working mothers, lack of support from family, information support from health workers and the surrounding environment. In 2023, in the work area of the Penfui Health Center, there are 177 working mothers who have babies or around 45.45%. The purpose of this study is to analyze factors related to the low coverage of exclusive breastfeeding in working mothers in the Penfui Health Center Area. This study is an analytical survey research using the Cross-Sectional method and a sample of 64 respondents. The data of this study was analyzed using the Chi Square test. The results of the study found that there was a significant relationship between maternal knowledge (p=0.046), information exposure (p=0.020), family support (p=0.044), health worker support (p=0.031) and low coverage of exclusive breastfeeding. There was a relationship between maternal occupation (p0.027) and infant health status (p=0.041), age (p=0.326) there was no significant relationship with low coverage of exclusive breastfeeding in the Penfui Health Center area. The conclusion in this study is that knowledge, information exposure and family support are related to exclusive breastfeeding. and the support of health workers, mothers' work and health status are related to the low coverage of exclusive breastfeeding in the work area of the Penfui Health Center. Mothers should further increase their awareness and willingness to provide exclusive breastfeeding even though they are busy with work to increase the coverage of Exclusive Breastfeeding.